2020
DOI: 10.1111/jfbc.13321
|View full text |Cite
|
Sign up to set email alerts
|

6ʹʺ‐p‐Coumaroylspinosin protects PC12 neuronal cells from acrylamide‐induced oxidative stress and apoptosis

Abstract: 6ʹʺ‐p‐coumaroylspinosin (P‐CS) is a flavonoid isolated from Ziziphi Spinosae Semen (ZSS), whereas, the antioxidative activity has not been reported. Oxidative stress is believed to be one of the main causes of neurodegenerative disorders. In this study, the antioxidative effect of P‐CS on PC12 cells was determined. The cells were treated with acrylamide (AA) in the absence or presence of P‐CS, and cell apoptosis was analyzed. Interestingly, P‐CS pretreatment of the cells could significantly prevent AA‐induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…), hydrogen peroxide (H 2 O 2 ), and hydroxyl radicals (OH • ) [12], of which H 2 O 2 is a culprit, destroying neurons, and thus is widely used as a stimulant of neutral cells to establish an in vitro oxidative injury model [13,14]. In addition, acrylamide, a vinyl monomer formed in high-temperature foods [15], is applied as a neurotoxin in various cell and animal models for its overproduction of ROS. For instance, acrylamide was suggested to induce cell apoptosis in human neuroblastoma SH-SY5Y cells [16] and promote neurotoxicity in the zebrafish model [17].…”
Section: Introductionmentioning
confidence: 99%
“…), hydrogen peroxide (H 2 O 2 ), and hydroxyl radicals (OH • ) [12], of which H 2 O 2 is a culprit, destroying neurons, and thus is widely used as a stimulant of neutral cells to establish an in vitro oxidative injury model [13,14]. In addition, acrylamide, a vinyl monomer formed in high-temperature foods [15], is applied as a neurotoxin in various cell and animal models for its overproduction of ROS. For instance, acrylamide was suggested to induce cell apoptosis in human neuroblastoma SH-SY5Y cells [16] and promote neurotoxicity in the zebrafish model [17].…”
Section: Introductionmentioning
confidence: 99%
“…In order to regulate the normal internal environment, cells are stable through a genetically spontaneous and orderly death called apoptosis 26 . It was reported that ACR exposure could activate the mitochondrial apoptotic pathway via activation of caspase 3 in PC12 cells and human neuroblastoma cells (SH‐SY5Y) 27,28 …”
Section: Resultsmentioning
confidence: 99%
“…Activation of caspase 9 was an early event in the mitochondrial involved apoptosis 5,32 . ACR has been reported that it could trigger the release of cleavage of caspase 9 and activate the mitochondrial apoptotic pathway in PC12 cells 27 . We used the activated caspase 9 antibody to determine the activated caspase 9 involved in the apoptosis pathway in PC12 and SK‐N‐SH cells treated with AA, ACR and AMPS.…”
Section: Resultsmentioning
confidence: 99%
“…Administration of 6ʹʺ-p-coumaroylspinosin (P-CS) (flavonoid isolated from Ziziphi Spinosae Semen) on PC12 neuronal cells significantly prevents acrylamide-induced cell death, decreases GSH content, and ROS overproduction. P-CS was also suppressing the expression of Bax (apoptosis regulator) and Bim (pro-apoptotic protein) induced by acrylamide and inhibits the JNKs pathway [16].…”
Section: Role Of Flavonoids In Oxidative Stressmentioning
confidence: 96%